Application of ultrasound in cardiovascular intervention via the distal radial artery approach: New wine in old bottles? - Chen, Tao; Yu, Xiaolong; Song, Ruixiao; Li, Lamei; Cai, Gaojun (Frontiers in Cardiovascular Medicine, 2022)
The distal radial artery (DRA) approach has emerged as a new approach in cardiovascular intervention. In recent years, ultrasound has been widely used in cardiovascular intervention via the DRA approach. This article systematically discusses the progress of ultrasound in the preoperative vascular assessment, intraoperative guided puncture and postoperative observation of complications via the DRA approach.